ZAQAH PROFESSION, OIL PALM PLANTS, AND COAL - Maulida, Sri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2019)
In the Qur’an the word ‘zakat’ is repeatedly mentioned, and it is always followed by the word ‘sholat’. It shows that Muslims have obligations not only limited to sholat, but also to zakat. There are many debates about zakat fitrah and zakat mal relating to legal matters and number of zakah. There are also many differences of opinion regarding to zakat profession, oil palm plants, and coal, so that the research needs to be conducted on this topic. It is interesting to be discussed because of the huge potential of oil palm plants and coal in South Kalimantan. In this research, the methods which are used are descriptive, comparative, deductive, and inductive. Based on the discussion in this article, it can be concluded that zakat profession is spesific characteristic of the verse purpose “....the good things which you have earned...” (Al-Baqarah: 267) and “Take alms of their wealth....” (AtTaubah: 103). Moreover, there is also the verse of Al-Baqarah: 267 “...and from that which We have produced for you from the earth....” This verse has spesific purpose from general purpose which is related to zakat of oil palm plants and coal.